Tinjauan teknik pengeringan dalam proses pemanasan untuk produksi pakan ternak - Najwa Hegyra Gumilar; Nyimas Popi Indriani; Abun (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
Drying is a crucial heat processing technique in animal feed production, used to reduce moisture content, extend shelf life, and maintain nutritional stability. Various methods have been applied, ranging from conventional convective drying (using ovens and solar energy) to advanced technologies such as microwave, infrared, freeze drying, vacuum, and hybrid drying. Each method has specific advantages and limitations in terms of energy efficiency, preservation of bioactive compounds, and effects on digestibility and feed palatability. This review examines the working principles of each method and their impact on nutrient quality, with a focus on process efficiency and the final feed value. Based on current literature, freeze and vacuum drying are superior in preserving heat-sensitive vitamins and compounds, while spray and fluidized bed drying enhance uniformity and feed intake. On the other hand, conventional techniques remain relevant due to their cost-effectiveness and simplicity. Therefore, when selecting a drying method, it is essential to consider the characteristics of the feed material and the formulation objective to ensure high-quality and sustainable feed production.